Directions of improving the implementation of controlling and diagnostic functions in the process of teaching «General Pedagogy» to students - Milash О (Problems of Engineer-Pedagogical Education, 2019)
The realization of the Concept for the implementation of the state policy in the sphere of general secondary education «New Ukrainian School» for the period until 2029 necessitates the improvement of the quality of pedagogical education. The article provides theoretical substantiation and defines practical means of improving the implementation of controlling and diagnostic functions while teaching the academic discipline «General Pedagogy» to students of higher pedagogical educational institutions in Ukraine. The necessity of using a binary approach in the process of teaching the academic discipline «General pedagogy», which, within the existing strategy to ensure guaranteed quality of education and professional standards laid down in the Law of Ukraine “On Higher Education”, provides for the formation of qualitatively new relations between teachers and students, enhancing the role of the latter in assessing the quality of the achievement of educational objectives. The article shows the importance of using competence-based and student-centered approaches, and determines that the implementation of the controlling and diagnostic functions can be improved by introducing new information and communication technologies into the educational process, in particular, in the process of exercising control and self-control of knowledge acquisition at all stages of learning. The author has worked out a system of requirements for the development and content of control tests as well as guidelines for the testing process. The paper also identifies the main advantages of this approach, which assures individuality, complexity, integrity, objectivity, adaptability, simplicity and manufacturability of the implementation of the diagnostic and controlling functions of the teacher.